Prevalence of Self-Harm Behaviors and Deliberate Self-Cutting in High School Students in Northern Iran and Its Relationship with Anxiety, Depression, and Stress - Elahe Abdollahi; Maryam Kousha; Arvin Bozorgchenani; Mohammadreza Bahmani; Elahe Rafiei; Fatemeh Eslamdoust-Siahestalkhi (Journal of Holistic Nursing and Midwifery)
Introduction: Self-harm has increased among adolescents in recent years, turning it to one of the major public and mental health concerns. Objective: The present study aims to investigate the prevalence of self-harm and deliberate self-cutting in high school students in northern Iran, and its relationship with anxiety, depression, and stress. Materials and Methods: In this analytical cross-sectional study, participants were 617 high school students in Rasht, Iran in 2018 who were selected through multistage cluster random sampling. Data collection tools were a demographic form, the Self-Harm Inventory (SHI), and the 21-item Depression, Anxiety, and Stress Scale (DASS-21). Data analysis was done by independent t-test, Kruskal–Wallis test, one-way analysis of variance, chi-square test, Fisher’s Exact test, and linear and logistic regression. Results: The mean age of students was 16.11±1.35 years, and the majority of them were male (64.2%). The prevalence of self-harm behaviors was 54.9% (n=339), 20.3% in females and 79.7% in males. Deliberate self-cutting was found in 11% of students. The score of SHI was significantly higher in boys than in girls, while the prevalence of deliberate self-cutting was more in girls (P=0.001). Self-harm behaviors increased with increasing depression, anxiety, and stress (P=0.001). Gender (B=0.704, 95%CI; 0.149-1.258, P=0.013), grade (B=-1.011, 95%CI;-1.517- -0.504, P=0.001), family size (B=0.620, 95%CI; 0.344-0.895, P=0.001), age (B=0.624, 95%CI; 0.286-0.962, P=0.001), and the grade point average in the past year (B=-0.945, 95%CI; -1.197- -0.693, P= 0.001) had significant relationship with self-harm behaviors (R2= 0.145). Moreover, gender (OR=4.874, 95%CI; 2.297-10.344, P=0.001), grade point average in the past year (OR=0.727, 95%CI; 0.567-0.932, P=0.012), substance abuse (OR=7.972, 95%CI; 3.424-18.564, P=0.001), depression (OR=1.163, 95%CI; 1.065-1.271, P=0.001), stress (OR=1.105, 95%CI; 1.006-1.213, P=0.036), and father’s educational level (OR=7.897, 95%CI; 1.138-54.807, P=0.001) had significant relationship with deliberate self-cutting. Conclusion: Self-harm behaviors in adolescents are associated with anxiety, depression, and stress.